Status prawny doktoranta w świetle ustawy Prawo o szkolnictwie wyższym. Student czy naukowiec? - Szwedziak-Bork, Ilona (Kwartalnik Prawa Publicznego, 2014)
This article considers the problem of determining the status of doctoral student that – in the current state of the law – is still under discussion. On the one hand, by analyzing the scheme of the Law on Higher Education doctoral student because of the multiplicity of identical rights and obligations is treated as a student. On the other hand, it should be pointed out that the scope of some of the rights and obligations situate doctoral students quite close to doctoral university researchers – or more specifically assistants. Attempt of resolving the current position of the doctoral student made in this article was done through the comparison of the rights and obligations of the doctoral student with the corresponding rights and obligations that the law enacts in relation to the above stated entities. The method adopted in the article allowed also illustrating the specificity of the doctoral student status in the current legal environment.